Prevalence of Pulmonary Tuberculosis, Failure of Treatment, and its Related Factors in Kashan During 2004-2017 - Atoof, Fatemeh; Marzhoseyni, Zeynab; Rashki, Somaye; Khaledi, Azad; Zamani, Mahboobeh; Hedayati, Mehrdad (Novelty in Biomedicine, 2023)
Background: Mycobacterium tuberculosis affects the lungs in 85% of all cases and the remaining 15% through extra pulmonary affecting other parts of the body such as lymph nodes, pleura, and the genitourinary system. This study aimed to investigate extra-pulmonary tuberculosis (TB) associated factors, failure of treatment, and trends between 2004-2017 in Kashan, Iran. Materials and Methods: This study was conducted during 2004-2017 on newly registered extrapulmonary tuberculosis patients referred to TB Referral Center in Isfahan province, Kashan city, Iran. Information (demographic characteristics, related factors of the disease, and treatment status) of 197 extrapulmonary tuberculosis (EPTB) patients was extracted from Medical case records. Results: In total, 527 cases of Tuberculosis were reported, of which, 159 (30.17%) were confirmed extrapulmonary TB. Eighty-five (53.5%) and 74 (46.5%) were male and female, respectively. Also, 74 (46.5%), and 84 (53.5%) of EPTB were from Iran, and Afghanistan immigrants, respectively. The average age of patients was 41.9±2.18. Among underlying diseases in extrapulmonary TB positive, diabetes mellitus (DM) was predominant with a prevalence of 31 (19.5%), while, 128 (80.5%) cases did not show any underlying disease. Most of the patients were in the age group (21-40 years) with a frequency of 60 (37.7%), and the lowest of patients belonged to the age group (>80 years) with a frequency of 9 (5.7%). No correlation was found between related factors and infection with EPTB (p> 0.05). Conclusion: Our findings showed that the prevalence of EPTB in Kashan was relatively high, but, a relative decrease was shown during 2004-2017, which with preventative measures can be reduced the prevalence.